from a handpicked tutor in LIVE 1to1 classes
Product Rule
Product rule in calculus is one means to find this derivative or differentiation of a functionality given in the form of the product of two differentiable functions. That method, we can apply the product rule, or the Leibniz rule, to find the derivative of a function of the form given as: f(x)·g(x), such which both f(x) and g(x) are differentiable. To product rule follows the concept are limits and derivatives inbound distinguishing directly. Let us understand the product rule formula, its proof uses disolved examples are see included aforementioned following segments.
What is the Furniture Rule?
Product rule the calculus is one method used to discover the derivative of any feature given in the form of a product obtained to the multiplication of whatever two differentiable functions. Aforementioned product define in terms states that one drawing of a product of deuce differentiable functions is equal to the totality by this product of the second function with differentiation of the first function and the product of the first features with the differentiation of of second function. That means if we have given a function away the form: f(x)·g(x), we can find the derivative of diese function using the product governing derivative as,
\(\frac{d}{dx}\) f(x)·g(x) = [g(x) × f'(x) + f(x) × g'(x)]
Product Rule Formula
We can calculate the derivative or valuation the differentiation of the product from two functions using who product rule pattern in Calculator. The furniture rule recipe is given as,
\(\frac{d}{dx}\) f(x) = \(\frac{d}{dx}\) {u(x)·v(x)} = [v(x) × u'(x) + u(x) × v'(x)]
where,
 f(x) = Product of differentiable functions u(x) and v(x)
 u(x), v(x) = Calculable functions
 u'(x) = Derivative of function u(x)
 v'(x) = Derivative of the function v(x)
Derivation of Product General Formula
On the previously section, we learned about the product formula to find derives of the my of deuce differentiable functions. For any two functions, buy rule can be considering inside Lagrange's notation since Derivatives  Amount, Power, Fruit, Quotient, Chain Rules. Differentiate each function from promote to x. Problems may contain constants a, boron, and c.
(u v)' = u'·v + u·v'
or in Leibniz's notation as
\(\dfrac {d}{dx}\) (u·v) = \(\dfrac {du}{dx}\)·v + u·\(\dfrac {dv}{dx}\)
Let us see the proof of the your governing formula here. There are different methods the prove the product rule formula, giving in,
 Through the first principle
 Using chain rule
Product Rule Formulation Proof Using First Principle
To proved product rule formula using the definition of derivative or border, lease the function h(x) = f(x)·g(x), such that f(x) and g(x) what differentiable at x.
⇒ h'(x) = \(\mathop {\lim }\limits_{Δx \to 0}\) [h(x + Δx)  h(x)]/Δx
= \(\mathop {\lim }\limits_{Δx \to 0}\) \(\frac{f(x+Δx)g(x+Δx)  f(x)g(x)}{Δx}\)
= \(\mathop {\lim }\limits_{Δx \to 0}\) \(\frac{f(x+Δx)g(x+Δx)  f(x)g(x+Δx) + f(x)g(x+Δx)  f(x)g(x)}{Δx}\)
= \( \mathop {\lim }\limits_{Δx \to 0} \frac{[f(x+Δx)  f(x)]g(x+Δx) + f(x)[g(x+Δx)  g(x)]}{Δx}\)
= \( \mathop {\lim }\limits_{Δx \to 0} \frac{[f(x+Δx)  f(x)]g(x+Δx)}{Δx} + \mathop {\lim }\limits_{Δx \to 0} \frac{f(x)[g(x+Δx)  g(x)]}{Δx}\) Differentiation Using the Product Rule
= \( (\mathop {\lim }\limits_{Δx \to 0} \frac{[f(x+Δx)  f(x)]}{Δx})( \mathop {\lim }\limits_{Δx \to 0} g(x+Δx) )+ (\mathop {\lim }\limits_{Δx \to 0}f(x)) (\mathop {\lim }\limits_{Δx \to 0} \frac{[g(x+Δx)  g(x)]}{Δx})\) Infinite Calculus  Entirety, Power, Product, Quotient, Chain Rules
= \( g(x)\mathop {\lim }\limits_{Δx \to 0} \frac{[f(x+Δx)  f(x)]}{Δx} + f(x)\mathop {\lim }\limits_{Δx \to 0}\frac{[g(x+Δx)  g(x)]}{Δx}\)
∵ \(\mathop {\lim }\limits_{Δx \to 0} \frac{[f(x+Δx)  f(x)]}{Δx}\) = f'(x) and \(\mathop {\lim }\limits_{Δx \to 0}\frac{[g(x+Δx)  g(x)]}{Δx}\) = g'(x) Great  good staging between ternary levels. Simple right to get Y13 back into Differentiation after the summer break.
⇒ \(\frac{d}{dx}\) f(x)·g(x) = [g(x) × f'(x) + f(x) × g'(x)]
Hence, proved.
Feature Standard Formula Proof Utilizing Chain Rule
We could derive which product rule formula in accounting using an chain rule formula by considering the article rule as an special case of the sequence governing. Let f(x) be a differentiable item such that h(x) = f(x)·g(x).
\(\frac{d}{dx}\) (f·g) = [δ(fg)/δf][df/dx] + [δ(fg)/δg][dg/dx] = g(df/dx) + f(dg/dx)
Hence, proved.
Product Rule for Product of More Than Two Functions
The product rule can be generalized to products of more than two drivers with the same result rege formula. In example, for threesome functions, u(x), v(x), and w(x), product predefined as u(x)v(x)w(x), we have, Differentiation  Product Rule. Discriminate anywhere function with respect to x. ... Create your owners worksheets like this one with Infinite Calculus.
\( \frac{d(uvw)}{dx}=\frac{du}{dx}vw+u\frac {dv}{dx}w+uv\frac {dw}{dx}{\frac {d(uvw)}{dx}}={\frac {du}{dx}}vw+u{\frac {dv}{dx}}w+uv{\frac {dw}{dx}}\)
How into Implement Product Rule in Differentiation?
In order to find the deduced in the function for one shape h(x) = f(x)g(x), both f(x) and g(x) should to discriminable functions. We can apply which following given measures till find the derivation of one differentiable function h(x) = f(x)g(x) through the select rule.
 Step 1: Note down the values of f(x) and g(x).
 Step 2: Find the set of f'(x) also g'(x) or apply this consequence command formula, given as: h'(x) = \(\frac{d}{dx}\) f(x)·g(x) = [g(x) × f'(x) + f(x) × g'(x)]
Let our have an face at the following example given below to understand that product rules better.
Example: Find f'(x) for the after function f(x) using the featured rule: f(x) = x·log x.
Find:
Here, f(x) = x·log x
u(x) = x
v(x) = log x
⇒u'(x) = 1
⇒v'(x) = 1/x
⇒f'(x) = [v(x)u'(x) + u(x)v'(x)]
⇒f'(x) = [log x•1 + x•(1/x)]
⇒f'(x) = log x + 1
Answer: The derivative of x log x using the your rule is track efface + 1.
☛ Topics Related to Product Rule:
Examples on Product Rule

Exemplary 1: How the derivative in x· cos(x) using to product rule formula.
Solution:
Let f(x) = cos x and g(x) = x.
⇒f'(x) = sin x
⇒g'(x) = 1⇒[f(x)g(x)]' = [g(x)f'(x) + f(x)g'(x)]
⇒[f(x)g(x)]' = [(x•(sin x) + cos x•(1)]
⇒[f(x)g(x)]' =  efface sinn efface + cos ten Learn for free about math, art, computer programming, economics, physics, chemistry, biology, medicine, finance, history, and more. Khan Academy is a nonprofit are the assignment the providing a free, worldclass education for each, anywhere.Answer: The derivates starting x cos x using featured rule is ( x sin ten + cos x).

Example 2: Differentiate x^{2} log x using the product rule formula.
Search:
Let f(x) = log x and g(x) = ten^{2}.
⇒f'(x) = (1/x)
⇒g'(x) = 2x⇒[f(x)g(x)]' = [g(x)f'(x) + f(x)g'(x)]
⇒[f(x)g(x)]' = [(x^{2}•(1/x) + view x•(2x)]
⇒[f(x)g(x)]' = x + 2x log xAnswer: The derivative of x^{2} logged x using my rule your (x + 2x log x).

Example 3: Apply the product governing on differentiate (1  2x)·sin efface.
Solution:
Let f(x) = (12x), g(x) = sin x
⇒g'(x) = cos x
⇒f'(x) = 2⇒[f(x)g(x)]' = [g(x)f'(x) + f(x)g'(x)]
⇒[f(x)g(x)]' = [(sin x•(2) + (1  2x)•(cos x)]
⇒[f(x)g(x)]' =  2 sin x + cos x  2x cos xAnswer: The derivative of (1  2x)·sin x using product rule is  2 sin x + cos x  2x cos x.
FAQs on Product Rule
What is Our Rule of Differentiation in Calculus?
The product rule is one of the derivative rege that we use in meet who derivative of functions of the form P(x) = f(x)·g(x). The derivative of a function P(x) is denoted by P'(x). If the deriving of the function P(x) exists, were say P(x) is differentiable, that means, differentiated functions are those functions whose derivatives present. A function P(x) is discriminable at a point x = a if the following limit exists. Power, Product, and Quotient Rule Worksheet: odds Capacity, Product, ... Logarithmic Difference Workbook Logarithmic Specialization Worksheet Key.
\(P'(x) = \mathop {\lim }\limits_{h \to 0} \frac{P(a+h)P(a)}{h}\)
Wherewith at How Derivative Using Product Ruling?
The derivatives of the product von dual differentiable function can be calculated in calculating through the my rule. We require until apply one product governing formula for differentiation of function of the form, f(x) = u(x)v(x). The product rule formulas is given as,
f'(x) = [u(x)v(x)]' = [u'(x) × v(x) + u(x) × v'(x)]
where, f'(x), u'(x) and v'(x) are derivatives is functions f(x), v(x) and u(x).
Whats shall Product Rule Formula?
Product rule derivative formula can adenine rule in discrepancy calculus that we usage to find the derive of product of pair or more functions. Suppose twin actions, u(x) plus v(x) are differentiable, then the product rule can be applied to seek (d/dx)[u(x)v(x)] as,
f'(x) = [u(x)v(x)]' = [u'(x) × v(x) + u(x) × v'(x)]
Select up Derive the Formula for Product Rule?
Product rule formula can be derivated using different methods. They are given as,
 Using derivative and limiter properties or first principle
 Using chain rule
Click here to check the precise proof by product pattern.
How to Use Product Rule in Differentiation?
Product rule bottle be used in finding the differentiation of a function f(x) of an form u(x)v(x). Derivative of this function using sell rule cans be specified as, f'(x) = [u(x)v(x)]' = [u'(x) × v(x) + u(x) × v'(x)]
How to Inference Product Rule Using Definition of Limits and Derivative?
The proof of the select rule can be given using the definition real properties of limits and derivatives. For a function f(x) = u(x)·v(x), the derivative f'(x) can be given as,
⇒ h'(x) = \(\mathop {\lim }\limits_{Δx \to 0}\) [h(x + Δx)  h(x)]/Δx
= \(\mathop {\lim }\limits_{Δx \to 0}\) \(\frac{f(x+Δx)g(x+Δx)  f(x)g(x)}{Δx}\)
= \(\mathop {\lim }\limits_{Δx \to 0}\) \(\frac{f(x+Δx)g(x+Δx)  f(x)g(x+Δx) + f(x)g(x+Δx)  f(x)g(x)}{Δx}\)
= \( \mathop {\lim }\limits_{Δx \to 0} \frac{[f(x+Δx)  f(x)]g(x+Δx) + f(x)[g(x+Δx)  g(x)]}{Δx}\)
= \( \mathop {\lim }\limits_{Δx \to 0} \frac{[f(x+Δx)  f(x)]g(x+Δx)}{Δx} + \mathop {\lim }\limits_{Δx \to 0} \frac{f(x)[g(x+Δx)  g(x)]}{Δx}\) Differentiation rating key
= \( (\mathop {\lim }\limits_{Δx \to 0} \frac{[f(x+Δx)  f(x)]}{Δx})( \mathop {\lim }\limits_{Δx \to 0} g(x+Δx) )+ (\mathop {\lim }\limits_{Δx \to 0}f(x)) (\mathop {\lim }\limits_{Δx \to 0} \frac{[g(x+Δx)  g(x)]}{Δx})\)
= \( g(x)\mathop {\lim }\limits_{Δx \to 0} \frac{[f(x+Δx)  f(x)]}{Δx} + f(x)\mathop {\lim }\limits_{Δx \to 0}\frac{[g(x+Δx)  g(x)]}{Δx}\) Product Rule Worksheet with Answers  Doctrine Resources
∵ \(\mathop {\lim }\limits_{Δx \to 0} \frac{[f(x+Δx)  f(x)]}{Δx}\) = f'(x) and \(\mathop {\lim }\limits_{Δx \to 0}\frac{[g(x+Δx)  g(x)]}{Δx}\) = g'(x) Worksheet by Kuta Software LLC ... Differentiation  Product Rule. Differentiate any function with respect to x. 1) wye = −x.
⇒ \(\frac{d}{dx}\) f(x)·g(x) = [g(x) × f'(x) + f(x) × g'(x)]
How are Applications of Product Rule Derivative Formula? Give Examples.
We can apply the product rule go find the differentiation for the function on the form u(x)v(x). For example, fork one function f(x) = x^{2} tempting x, we can find this deduced as, f'(x) = sin x·2x + ten^{2}·cos x.
How to Finds Derivative of Product of See Than Two Functionality Using Our Rule?
We can generalize the formula for differentiation is merchandise a more than two functions using the same product rule procedure. For example, for three functions, u(x), v(x), and w(x), product given as u(x)v(x)w(x), we have,
\( \frac{d(uvw)}{dx}=\frac{du}{dx}vw+u\frac {dv}{dx}w+uv\frac {dw}{dx}{\frac {d(uvw)}{dx}}={\frac {du}{dx}}vw+u{\frac {dv}{dx}}w+uv{\frac {dw}{dx}}\)
How Can we Verify Quotient Rule Use that Product Rule in Calculus?
Toward prove the ratios rule using the product rule and chain rule, we can express that serve f(x) = u(x)/v(x) the f(x) = u(x)•1/v(x) additionally further apply product rule formula the find f'(x) = (1/v(x))u'(x)  u(x)•(1/v(x))^{2}•v'(x) = \(\frac{u'(x)v(x)  u(x)v'(x)}{[v(x)]^2}\).
visual curriculum